TEACHING GENETICS THROUGH DIFFERENTIATED SCIENCE INQUIRY BASED ON RESEARCH RESULTS OF GENE VARIATION ANALYSIS TO INCREASE COGNITIVE LEARNING OUTCOMES UNDERGRADUATE BIOLOGY STUDENT - M Amien Rais; Mohamad Amin; Betty Lukiati (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2021)
Paradigm change in 21st century poses a challange for higher education in teaching science as inquiry. In another side, teaching science as inquiry meet some problem because of every student in the classroom was different. This research is aimed to know effectiveness of differentiated science inquiry based on research results of gene variation analysis in genetics course to increase students cognitive learning outcome. This research used pre-experimental research design on one class that consist of 26 biology students. Statistical analysis used in this study is paired sample t-test on pre-test and post-test to measure students cognitive learning outcomes. If there are significances between the pretest and posttest, data analysis was continue to N-Gain score to determine the increasing category of students cognitive learning outcome. The average pretest score was 64,3 and posttest score was 77,2. The statistical analysis result showed there was a significant difference between students cognitive learning outcome (p<0,005), meanwhile the N-Gain score between pretest and postest is 36,2 and categorized a medium criteria. That result mean although there are difference students learning outcome before and after learning by using differentiated science inquiry model based on research result of gene variation analysis, that learning is not too recommended to increase students cognitive learning outcome.